2018
DOI: 10.1038/s41598-018-33048-z
|View full text |Cite
|
Sign up to set email alerts
|

How phosphorylation influences E1 subunit pyruvate dehydrogenase: A computational study

Abstract: Pyruvate (PYR) dehydrogenase complex (PDC) is an enzymatic system that plays a crucial role in cellular metabolism as it controls the entry of carbon into the Krebs cycle. From a structural point of view, PDC is formed by three different subunits (E1, E2 and E3) capable of catalyzing the three reaction steps necessary for the full conversion of pyruvate to acetyl-CoA. Recent investigations pointed out the crucial role of this enzyme in the replication and survival of specific cancer cell lines, renewing the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 70 publications
0
24
1
Order By: Relevance
“…PDH is one of the three enzymatic subunits (E1, E2, and E3) forming the pyruvate dehydrogenase complex (PDC) that catalyzes the conversion of pyruvate in Acetyl-CoA. Particularly, PDH (corresponding to E1 subunit) catalyzed pyruvate decarboxylation which is the first step in the conversion of pyruvate in Acetyl-CoA [ 22 ]. It has been reported that PDH activity is greatly decreased in cachectic conditions [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…PDH is one of the three enzymatic subunits (E1, E2, and E3) forming the pyruvate dehydrogenase complex (PDC) that catalyzes the conversion of pyruvate in Acetyl-CoA. Particularly, PDH (corresponding to E1 subunit) catalyzed pyruvate decarboxylation which is the first step in the conversion of pyruvate in Acetyl-CoA [ 22 ]. It has been reported that PDH activity is greatly decreased in cachectic conditions [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Phosphorylation of Ser232 is seen to behave very differently compared to Ser293 and Ser300, with the phosphorylation level increasing even during lactate consumption. [36] used a molecular dynamics method and could not identify inhibitory effects due to pSer232 in the cases where pSer293 and pSer300 inhibited enzyme activity [36]. Although in vitro studies have shown that the phosphorylation of any of the three Ser residues on the E1α subunit of PDC leads to the deactivation of the enzyme complex [35], pSer293 was found to have the most potent inhibitory effect [58, 59].…”
Section: Resultsmentioning
confidence: 99%
“…Further insights into the highly dynamic nature of PDC as a multienzyme complex could be achieved using mathematical modeling approaches. [36] used molecular dynamic simulations to test the structural consequences of the phosphorylation on PDCE1α. They found that phosphorylations of Ser293 and Ser300 change the PDCE1α catalytic site [36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PDC activity is mainly regulated via the phosphorylation of the E1 component with regulation independent of phosphorylation also reported. 11,3134 Inactivation of the E1 component of human PDC is achieved via phosphorylation of E1α S203, S264, and S271 located on loops formed by E1α amino acid stretches R259-R282 (Loop A, highly conserved) and N195-E205 (Loop B, highly conserved) (Figure 1). 11,31,32,35,36 E1α S264 is the most rapidly phosphorylated site.…”
Section: Introductionmentioning
confidence: 99%